2016
DOI: 10.18203/2319-2003.ijbcp20161536
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of knowledge, attitude and practice of self-medication among medical and para medical students in a medical college, Mangaluru, Karnataka, India

Abstract: A comparative study of knowledge, attitude and practice of self-medication among medical and para medical students in a medical college, Mangaluru, Karnataka, India INTRODUCTIONSelf-medication, an important component of self-care, is the most common practice in developing countries. It is defined as the use of drugs to treat self-diagnosed illnesses or irregular use of a prescribed drug for a chronic disease. Traditionally, self-medication is described as the use of drugs, herbs or home remedies on advice of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Diarrhea is a symptom of infection of the intestinal tract, which can be caused by a variety of bacterial, viral, and parasitic organisms [7][8][9][10][11][12][13]. The infection usually spreads through contaminated food, drinking unfiltered and untreated water, or from person to person as a result of poor hygiene [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diarrhea is a symptom of infection of the intestinal tract, which can be caused by a variety of bacterial, viral, and parasitic organisms [7][8][9][10][11][12][13]. The infection usually spreads through contaminated food, drinking unfiltered and untreated water, or from person to person as a result of poor hygiene [1].…”
Section: Introductionmentioning
confidence: 99%
“…But still, it is found that many people take overthe-counter medication to relieve symptoms, and frequently, medical students self-administer medicine for the treatment of diarrhea without any consultation from the physician. Medical students in developing countries, such as India, often resort to self-administering medications without proper medical supervision, as indicated by a study in PMC [10,11].…”
Section: Introductionmentioning
confidence: 99%